Comparing the Effects of Duo-Functional Triple-Layer Films Enriched with Different Sources of Curcumin on the Shelf-Life of Fish - Joanna Tkaczewska; Piotr Kulawik; Nikola Nowak; Wiktoria Grzebieniarz; Paweł Krzyściak; Wondyfraw Tadele; Eskindir Endalew Tadesse; Rafał Szram; Paulina Guzik; Ewelina Jamróz (Foods)
The objective of this study was to compare the effects of two types of active triple-layer films containing curcumin on the shelf-life of salmon fillets. One film (Film A) contained pure curcumin dissolved in lemongrass essential oil, while the other (Film B) incorporated curcumin from Curcuma longa extract dissolved in citral. The impact of these active films on the preservation of salmon fillets quality and safety was studied by analyzing factors such as color parameters, sensory evaluation, lipid oxidation, and biogenic amines. Despite good active properties measured in vitro, both films harmed the sensory quality and color of salmon. However, the incorporation of active ingredients in biopolymer films has shown the potential to inhibit biogenic amine formation. The findings pave the way for future research to explore the synergistic effects of combining various natural extracts with active packaging films.